Factors affecting students' self regulated learning using learning management system - Hashemyolia, Shayesteh; Asmuni, Azizan; Mohd Daud, Shaffe; Mohd Ayub, Ahmad Fauzi; Arif Shah, Jasmin (IDOSI Publications, 2014)
In blended learning, student’s engagement is important in the learning outcomes because it predicts student academic progress and achievement. The low rate of student’s engagement in Learning Management System (LMS) is a very important issue and there is a need to examine the factors affecting it. The Self Regulating Engagement or self regulated learning strategies (SRL) that is metacognitive and cognitive learning strategies to complete a task is as an important variable for explaining students’ performance and engagement in online learning. There are many factors influencing the SRL as shown by past research. However, a more stable predictor of SRL need to be studied in the context of LMS. Thus this paper is deliberated with the objective of determining technology learning environment factors affecting SRL among students. The dependent variable is SRL (motivation, cognitive, metacognitive and resource management) and the independent variables are technology learning environments. This study shall be beneficial for the university in facilitating effectively the online learning activities through the application of LMS.